The construction of knowledge about African musical instruments from musical iconography in European writings from the 16th to the 20th century - (:unkn) unknown (My University, 2022)
In the accounts of travellers and ancient musical treatises, the visual representations of African instruments and the content of the texts in which the images are inserted are a valuable complement to the instruments in museums. These images offer greater historical depth than the instruments collected. The written sources from which the illustrations are taken often contain information about their context, which museum objects rarely offer.
Keywords: African Research